Poverty Trend and its Indicators in Nepal: A Descriptive Analysis - Lamichhane, Basu Dev; Chalise , Mahananda; Neupane, Dasarath (NPRC Journal of Multidisciplinary Research, 2026)
Background: Poverty encompasses not just people's dire economic circumstances but also humanity's cultural, ethical, social, political, psychological, and economic needs. It is one of the upsetting situations that people in underdeveloped nations deal with regularly. Objectives: The study aims to examine the causes, trends, and impacts of poverty in Nepal by focusing on key macroeconomic factors such as low-income levels. Despite gradual economic progress in recent years, poverty remains a major challenge affecting a large portion of the population, particularly in rural and remote areas, with unemployment, unequal distribution of resources, and limited access to education and health services. Secondary data collected from government reports, national surveys, and international organizations are used for analysis. Research Design: The study applies descriptive and analytical methods, supported by tables, figures, and charts, to present the poverty situation clearly.Finding: The study's findings reveal that structural weaknesses in the economy, dependence on agriculture, and regional disparities significantly contribute to persistent poverty. Conclusions:  The research concludes that effective government policies, employment generation, investment in human capital, and inclusive economic growth are crucial for reducing poverty and enhancing living standards in Nepal. Additionally, the study also discusses the trends and measurement of poverty in Nepal.Novelty: This study goes beyond income-based analysis to explain chronic poverty in Nepal by integrating macroeconomic, structural, and regional factors in a novel way. It offers policy-relevant information to enable targeted poverty reduction efforts and efficient measures of poverty.Implication: The study's findings could be useful for policymakers, regulators, and other stakeholders in developing a strategic framework (SF) for measuring and alleviating poverty.